Metal complexes derived from tetradentate Schiff base ligands: Synthesis, spectroscopic analysis, thermogravimetric degradation and antimicrobial activities - Hezam, Abdulbari; Unlu, Seda; Elmali, Fikriye Tuncel (ELSEVIER, 2023)
In the present study a series of compounds which consist of two novel Schiff base ligands (L1 and L2) and their cupper, nickel and cobalt complexes (L1-Cu, L1-Ni, L1-Co, L2-Cu, L2-Ni, L2-Co) were synthesized under argon atmosphere. 4-aminomethylpyridine and 4-aminoquinoline were used as primary amines for the syntheses of L1 and L2, respectively, 2,2 & PRIME;-[propane-1,3-diylbis(oxymethylene)]dibenzaldehyde was used as carbonyl compound for both L1 and L2. The structures of synthesized compounds determined by FT-IR, ESI-MS and 1HNMR spectro-scopic techniques. TGA-DSC technique was used to determine the thermal decomposition of all synthesized compounds. L1, L1-Ni, L1-Co, L2, L2-Co began to decompose at 250 degrees C, L1-Cu and L2-Cu at 200 degrees C, L2-Ni at 300 degrees C. In vitro Antimicrobial activities of ligands and complexes have been evaluated against three Gram -positive, three Gram-negative bacteria and a fungus using the broth microdilution method. The synthesized compounds possessed the activity against all examined microorganisms having the minimum inhibitory con-centration (MIC) values between 9.7 and 5000 & mu;g/mL. L2 and L2-Co showed the best antibacterial activity against S. epidermidis and S. aureus with the low MIC value of 9.7 & mu;g/mL.
Keywords: 4-aminoquinoline; Schiff base; Complex; Antibacterial activity; Thermogravimetric analysis; BIOLOGICAL-ACTIVITY; IN-VITRO; ANTIBACTERIAL; DERIVATIVES; ANTIFUNGAL; RU(II); Chemistry